Inclusion complex with β-cyclodextrin is a key determining factor for the cardioprotection induced by usnic acid. (1st December 2020) - dos Santos, Péligris Henrique; Mesquita, Thassio; Miguel-dos-Santos, Rodrigo; de Almeida, Grace Kelly Melo; de Sá, Lucas Andrade; dos Passos Menezes, Paula; de Souza Araujo, Adriano Antunes; Lauton-Santos, Sandra
Abstract: Ischemia-reperfusion (I/R) injury causes oxidative stress, leading to severe cardiac dysfunction. Thus, biologically active compounds with antioxidant properties may be viewed as a promising therapeutic strategy against oxidative-related cardiac disorders. Usnic acid (UA), a natural antioxidant, was complexed with β-cyclodextrin (βCD) to improve its bioavailability. Wistar male rats were orally treated with the free form of UA (50 mg/kg) or the inclusion complex UA/βCD (50 mg/kg) for seven consecutive days. Afterward, hearts were subjected to I/R injury, and the cardiac contractility, rhythmicity, infarct size, and antioxidant enzyme activities were evaluated. Here, we show that neither UA nor UA/βCD treatments developed signs of toxicity. After I/R injury, animals treated with UA/βCD showed improved post-ischemic cardiac functional recovery while the release of cell injury biomarkers decreased. Following reduced cardiac damage, a lower incidence of ventricular arrhythmias and smaller myocardial infarct size were associated with reduced lipid peroxidation, along with preserved activity of antioxidant enzymes compared to untreated rats. Surprisingly, uncomplexed UA did not protect hearts against IR injury. Altogether, our results indicate that the inclusion complex UA/βCD is a critical determining factor responsible for the cardioprotection action of UA, suggesting the involvement of an antioxidant-dependent mechanisms. Moreover, our findings support that UA/βCD is a structurally engineered compound with active cardioprotective properties. Graphical abstract: Image 1 Highlights: UA/βCD inclusion complex enhances the aqueous solubility of UA. Uncomplexed UA has no cardioprotective properties. UA/βCD inclusion complex protects hearts against myocardial IR injury. UA/βCD is a structurally engineered compound with active cardioprotective properties.